PENGARUH KEMUDAHAN PENGGUNAAN, KEJELASAN INFORMASI, DAN KETERSEDIAAN FITUR LAYANAN SISTEM ISELLERSHOP TERHADAP KEPUASAN MAHASISWA PADA PEMESANAN TOGA DI KOPMA UNNES - Feriyoga Khoirunnas; Hengky Pramusinto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
KOPMA UNNES implemented the iSellerShop system to streamline graduation gown ordering. However, students still encounter issues such as confusing workflows, unclear information, and limited transparency features, which potentially diminish user satisfaction. This study aims to analyze the influence of ease of use, information clarity, and service feature availability on student satisfaction. Employing a quantitative explanatory approach, data were gathered from 100 respondents and analyzed using PLS-SEM. Findings reveal that ease of use and information clarity significantly and positively impact satisfaction. Conversely, service feature availability has no significant effect, as users prioritize core functionality and information accuracy over supplementary features. This study emphasizes that simplifying systems and enhancing information quality are crucial for maintaining user satisfaction in campus digital services.